THE CORRELATION BETWEEN THE LEVEL OF KNOWLEDGE ABOUT CERVICAL CANCER PREVENTION AND IVA EXAMINATION RESULTS IN THE COASTAL COMMUNITY OF WAAI, CENTRAL MALUKU REGENCY, MALUKU PROVINCE - Debora Hetharia (Jurnal Medika Hutama, 2026)
Cervical cancer remains one of the leading causes of death among women, especially in developing countries such as Indonesia. Visual Inspection with Acetic Acid (VIA) is an effective, simple, and appropriate method of early detection for regions with limited resources. The level of public knowledge about cervical cancer prevention greatly influences the success of IVA screening programs. Coastal communities, including those in Negeri Waai, Central Maluku Regency, face geographical, social, and cultural barriers that can reduce participation in screening. This study aims to determine the relationship between the level of knowledge about cervical cancer prevention and IVA screening results in coastal communities in Negeri Waai, Maluku Province. This study used a quantitative approach with a cross-sectional correlational design. The sample consisted of 40 women who were married or sexually active. Knowledge levels were measured using a standardized questionnaire, while IVA results were obtained from examinations by trained health workers. Data analysis was performed using Pearson's correlation test. The results showed a significant negative correlation between knowledge level and IVA examination results (r = –0.501; p = 0.001). This means that the higher the respondents' knowledge level, the less likely the IVA examination results would indicate precancerous abnormalities. These findings emphasize the importance of increasing community knowledge as an effort to prevent and detect cervical cancer early in coastal areas.